2010
DOI: 10.1598/rt.64.3.2
|View full text |Cite
|
Sign up to set email alerts
|

“High 5!” Strategies to Enhance Comprehension of Expository Text

Abstract: This article reviews theoretical and research evidence to support the explicit and systematic teaching of five comprehension strategies that will help all students tackle expository texts with success. The article explains the “High 5!” strategies and how to teach them. An example of a lesson is included to show how the five strategies connect with students' background knowledge to enhance comprehension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 5 publications
0
18
1
6
Order By: Relevance
“…This preteaching of vocabulary is especially important for struggling readers because students who have strong vocabularies understand more of what they read and learn more vocabulary through reading (Berkeley & Scruggs, 2010;Cunningham & Stanovich, 1998). Previous research found a wide range of text structures within and across textbooks (e.g., Dymock & Nicholson, 2010); however, we found a large number of descriptive structures across texts. In addition, the range of 22% to 36% of unclear text structures across all chapters examined in this study is noteworthy.…”
Section: Instruction To Supplement Textbook Features That Thwart Compcontrasting
confidence: 74%
“…This preteaching of vocabulary is especially important for struggling readers because students who have strong vocabularies understand more of what they read and learn more vocabulary through reading (Berkeley & Scruggs, 2010;Cunningham & Stanovich, 1998). Previous research found a wide range of text structures within and across textbooks (e.g., Dymock & Nicholson, 2010); however, we found a large number of descriptive structures across texts. In addition, the range of 22% to 36% of unclear text structures across all chapters examined in this study is noteworthy.…”
Section: Instruction To Supplement Textbook Features That Thwart Compcontrasting
confidence: 74%
“…Par exemple, contrairement au texte narratif, la lecture du texte informatif n'exige pas toujours une lecture linéaire ; elle invite plutôt le lecteur à une exploration du texte non nécessairement séquentielle. L'enseignant peut montrer cet aspect particulier en attirant l'attention des élèves sur les illustrations, les diagrammes, les sous-titres ou d'autres éléments du texte, tout en modélisant, en contexte, les stratégies qui soutiennent la compréhension, telles que déterminer son intention de lecture, activer ses connaissances antérieures, analyser la structure du texte, se questionner avant, pendant et après la lecture, se faire des images mentales, faire des inférences et résumer l'information en lisant (Dymock et Nicholson, 2010). Bien que des stratégies analogues soient nécessaires lors de la lecture de textes narratifs, il n'en demeure pas moins qu'il existe des différences dans le traitement de l'information que proposent ces différents genres de textes (Graesser et Goodman, 1985).…”
Section: L'importance De Lire Des Textes Informatifs Aux éLèvesunclassified
“…D'autres auteurs ont développé des modèles pour guider les pratiques d'enseignement faisant usage de ces textes (Dymock et Nicholson, 2010 ;Palmer et Stewart, 2005 ;Stead, 2014) ou des critères pour juger de leur qualité (Atkinson et al, 2009). Cependant, les facteurs qui orientent les choix des enseignants lors de la sélection des textes lus aux élèves, de même que leurs conceptions des défis ou des avantages associés à l'usage des textes informatifs comme soutien à cette activité semblent être peu étudiés.…”
Section: La Sélection Des Textes Informatifs Pour La Lecture Aux éLèvesunclassified
See 1 more Smart Citation
“…• Using video games and multimedia as tools for teaching writing (Gerber & Price, 2011;Heaven, 2014;Proske, Roscoe & McNamara, 2014), • Using multisensory stimuli to enhance the quality of reading comprehension (Baines, 2008(Baines, , 2013Dymock & Nicholson, 2010;Laitusis, 2010), • Using multimedia to teach listening and speaking skills (Fisher & Frey, 2014;Nguyet & Mai, 2012;Skouge, Rao & Boisvert, 2007).…”
Section: New Toolsmentioning
confidence: 99%